Formulación de estrategias para fortalecer el sistema administrativo y de distribución de funciones en el Hospital del IESS - CHONE. - Rodríguez Pinargote, Mónica Paola (2010)
This research work entitled DEVELOPING STRATEGIES TO STRENGTHEN THE SYSTEM ADMINISTRATION AND DISTRIBUTION OF FUNCTIONS IN THE HOSPITAL OF SOCIAL Security Institute Chon, collects information on how the service takes effect that gives its members, establishing mechanisms research, interviews and surveys that happiness institution determined that administrative changes should be made to provide a provision involving optimal. The proposal as linking strategies and improvement have been provided through research allow proper performance of tasks and functions performed by employees and officials of the hospital, to provide a service prompt and efficient attention. The social responsibility of the institutions of public health is prevention, care and recovery of its affiliates, the same must be of quality, as enshrined in the current Constitution of the Republic of Ecuador (2008) (SEE ANNEX # 1). The reasons for this topic was based on the low satisfaction are members of the SSC (Seguro Social Campesino) and / or the G88 (General Social Security) who are at the time of going to medical appointments. The strategies aim to ensure that employees and officials provide a better service how right of all Ecuadorians, thus allowing affiliates result in better served and consequently better health in them.